ORGANIZATIONAL AND ECONOMIC ASPECTS OF INFORMATION AND ANALYTICAL SECURITY PROVISION OF TRADE ENTERPRISES: A STRATEGIC APPROACH - VIVCHAR, Viktor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the theoretical foundations and applied dimensions of ensuring the information and analytical security of trade enterprises under contemporary economic, technological, and competitive conditions. The study emphasizes that the growing complexity of retail operations, digitalization of business processes, and intensification of external and internal threats significantly increase the demand for high-quality analytical support within enterprise security systems. A structural and logical framework for organizing information and analytical support is developed, reflecting the interconnection between data acquisition, processing, analysis, and managerial decision-making.The article substantiates a set of conditions that must be considered in designing an effective information and analytical security system, including the availability of reliable data flows, integration of digital technologies, adequate regulatory support, and the formation of organizational competencies required for secure and effective information management. Based on these prerequisites, a mechanism for ensuring information and analytical security in trade enterprises is proposed, which incorporates strategic planning, risk identification, monitoring tools, and preventive and response measures.Furthermore, the study outlines practical measures aimed at strengthening information and analytical security, such as enhancing cybersecurity protocols, optimizing internal information policies, introducing advanced analytical platforms, and improving staff competencies in risk-oriented management. The article also presents an approach to assessing the economic efficiency of implementing such systems, highlighting cost reduction, improved decision quality, and strengthened enterprise resilience as key outcomes.
Keywords: commercial enterprises; enterprise security; economic security; management system; retail trade; entrepreneurship; information and analytical subsystem; information and analytical security support